2014
DOI: 10.1016/j.virol.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus infection induces G1 to S phase transition in MA104 cells via Ca+2/Calmodulin pathway

Abstract: Viruses, obligate cellular parasites rely on host cellular functions and target the host cell cycle for their own benefit. In this study, effect of rotavirus infection on cell cycle machinery was explored. We found that rotavirus (RV) infection in MA104 cells induces the expression of cyclins and cyclin dependent kinases and down-regulates expression of CDK inhibitors, resulting in G1 to S phase transition. The rotavirus induced S phase accumulation was found to be concurrent with induction in expression of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 65 publications
4
18
0
Order By: Relevance
“…The trend of p21 follows the same pattern as that of p53-a decline during the span of 2-8 hours followed by restoration. Regulation of p21, however, was found to be transcriptional and not because of global translational arrest [130]. Concurrent with a previous report of overall activation of transcription factor AP1 [46], a sharp upregulation of c-fos was observed at 6 and 9 hours post RV infection.…”
supporting
confidence: 78%
“…The trend of p21 follows the same pattern as that of p53-a decline during the span of 2-8 hours followed by restoration. Regulation of p21, however, was found to be transcriptional and not because of global translational arrest [130]. Concurrent with a previous report of overall activation of transcription factor AP1 [46], a sharp upregulation of c-fos was observed at 6 and 9 hours post RV infection.…”
supporting
confidence: 78%
“…It suggested that CD38 may induce G1 to S phase transition in cervical cancer cells and contribute to promote cell proliferation rate. The P21鈥恈yclinD1鈥怌DK4/6 pathway promotes G1 to S stage transition, and this pathway is commonly dysregulated in a large number of carcinomas . In our study, we found there is a negative relationship between CD38 and P21, and a positive relationship between CD38 and CDK4/cyclinD1 both in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 56%
“…The P21-cyclinD1-CDK4/6 pathway promotes G1 to S stage transition, and this pathway is commonly dysregulated in a large number of carcinomas. 33 In our study, we found there is a negative relationship between CD38 and P21, and a positive relationship between CD38 and CDK4/cyclinD1 both in vivo and in vitro. We speculated that with the over-expression of CD38, P21 was down-regulated which led to an up-regulation of cyclinD1.…”
Section: Discussionsupporting
confidence: 56%
“…Successful infection entails subversion of antiviral immune responses (Graff, Mitzel, Weisend, & Flenniken, ; Barro & Patton, ; Graff, Ettayebi, & Hardy, ), evasion of pre鈥恗ature apoptosis (Bagchi et al, ; Bagchi, Nandi, Nayak, & Chawla鈥怱arkar, ; Chanda et al, ), avoidance of stress response (Trujillo鈥怉lonso, Maruri鈥怉vidal, Arias, & L贸pez, ; Zambrano et al, ) and preferential synthesis of viral proteins and nucleic acids (Groft and Burley, ; Piron, Delaunay, Grosclaude, & Poncet, ; Piron, Vende, Cohen, & Poncet, ; Vende, Piron, Castagn茅, & Poncet, ), all of which converge to a central strategy employed by viruses鈥恡o usurp host machinery in favor of viral perpetuation. Indeed, heavy reliance of RV multiplication on host protein chaperone system (Dutta et al, ; Dutta et al, ), intracellular calcium metabolism (Chattopadhyay et al, ), intercellular tight junction function (Torres鈥怓lores, Silva鈥怉yala, Espinoza, L贸pez, & Arias, ), cell鈥恈ycle machineries (Bhowmick, Banik, Chanda, Chattopadhyay, & Chawla鈥怱arkar, ), ubiquitin鈥恜roteasome system (L贸pez, Silva鈥怉yala, L贸pez, & Arias, ), and endocytosis components (Silva鈥怉yala et al, ) have been reported.…”
Section: Introductionmentioning
confidence: 99%